SISTEM INFORMASI GMC FITNESS - , PRADIANCE MINDOWARDO DUHA; , Muhammad Fakhrurrifqi, M.Cs. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
GMC fitness is one of medium that GMC Health Center GadjahMada University has. In this case, GMC fitness manage data by hand-written (using paper and pen), so it causes some problems. One of the problems is in reporting data of visitor who visit GMC fitness, participant attendance, training program, fitness instruments and it is reporting in Microsoft excel form. GMC fitness information system is built by using Webserver XAMPP, basis data MySQL, and PHP programming language with Framework Codeigniter. This system information handle in processing the data of participants (visitors), attendance list, training program, fitness instruments and its reporting. This system information is proven that it can make easier to processing the data such as process of participant registration, participant attendance, training program, fitness instruments and it is reporting in Microsoft excel form.